Analysis Of Product Price For Creative Economic Business Yogyakarta Special Region Using Data Scrapping - Astika Ayuningtyas; Yuliani Indrianingsih; Uyuunul Mauidzhoh (Information Technology and Science (ITScience), 2023)
The government in the National Economic Recovery (PEN) launched a strategy to increase business activity, namely by maximizing the potential for product sales through E-Commerce. E-Commerce sites in Indonesia display product information with different descriptions and prices. Through the pages on E-Commerce can collect data to form a useful information. Collection of data variations requires a method or system that can automatically collect the data provided on the Web page. In addition to data collection, another thing that needs to be considered is the meaning of knowledge from the collection of information that has been obtained. For these data to be useful, it is necessary to design a place for data management. Data must be selected and arranged properly so that it is easy to use so that it gives a good meaning. This research requires methods and tools in the process. The method used is Web Scrapping while the tools used are Tableau. There are two objectives in this research. First, obtain product price data for creative economy entrepreneurs in the Special Region of Yogyakarta through E-Commerce, especially Tokopedia and Bukalapak. Second, present product price data visually to facilitate the process of price distribution analysis so that it can provide information to local governments, especially product managers from creative economy business actors to support strategic policies in determining product prices from creative economy business actors in the Special Region of Yogyakarta to support promotion and tourism.